Program Sarigabah (Satu Hari Tiga Bahasa) Sebagai Upaya Pelestarian Budaya dan Penguatan Multibahasa: Studi Kasus di SDN 1 Mangkujayan - Lailatul Hidayati; Ahmad Mu'is; Rahmat Prayogi; Syaiful Kiram (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Globalization has contributed to a decline in children's familiarity with local languages and cultures. This situation calls for educational strategies that preserve local heritage while fostering early multilingual skills. This study explores the meaning and implementation of the Sarigabah (One Day, Three Languages) program at SDN 1 Mangkujayan as a cultural preservation and multilingual education effort. Using a qualitative case study approach, data were collected through interviews, observations, and documentation involving three teachers and six students. The findings show that Sarigabah integrates the use of Indonesian, Javanese, and English within a single school day according to a set schedule. The inclusion of Reog Ponorogo traditional attire enhances cultural values. Teachers and students actively participate, show pride, and develop greater confidence in using both local and foreign languages. The program fosters a culturally rich, multilingual learning environment. Thus, Sarigabah is an effective model of local wisdom-based education to address global challenges.